2008
DOI: 10.1590/s1677-54492008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Implante de filtro em veia cava inferior dupla: relato de caso e revisão da literatura

Abstract: Double inferior vena cava is a rare anatomic variation with prevalence ranging between 0.2-3.0%. In cases of duplication, inferior vena cava filter placement options include placing it in both vena cava, coil-embolization of the intervenous segment plus placing a filter in the right inferior vena cava, or suprarenal filter placement. We report a case of deep venous thrombosis after unilateral primary total hip replacement, presenting with contraindications for anticoagulant therapy, in which cavography showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…The proportion of anatomic variations found in this study was greater than is described in the literature, 7,14,19,20 since two patients had duplication of the inferior vena cava in the infrarenal region (1% do total) and three patients (2% of the total) had a single renal vein feeding a single kidney.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The proportion of anatomic variations found in this study was greater than is described in the literature, 7,14,19,20 since two patients had duplication of the inferior vena cava in the infrarenal region (1% do total) and three patients (2% of the total) had a single renal vein feeding a single kidney.…”
Section: Discussioncontrasting
confidence: 52%
“…Duplicated caval veins should be identified since filter placement can be ineffective in these rare cases. [6][7][8] The objective of this study was to establish parameters for the relationship between the renal veins and the infrarenal vena cava and their corresponding vertebral bodies, their relationships with biotypes and anatomic variations; the relationships between the vertebral bodies and the confluence of the common iliac veins into the vena cava and the distance between this bifurcation and the outflow of the more distal renal vein, with reference to placement of vena cava filters.…”
Section: Introductionmentioning
confidence: 99%
“…11 Zhu Tong et al 15 reported two cases of vena cava filter implantation that were ineffective at preventing pulmonary embolization because of unknown IVC duplication in the patients. 15 In Brazil, Malgor et al 16 report placing an IVC filter in a suprarenal position after cavography showed that the vessel was duplicated and also reported that the filter effectively prevented pulmonary embolism. 16 Although several different diagnostic methods are under analysis for their potential to identify and diagnose PVC, including transvaginal ultrasound, computed tomography, and magnetic resonance, 4,6 angiography is still the gold standard, for diagnosis both of PVC and of anatomic anomalies of the IVC and iliac veins, because it enables assessment of the different flow patterns and also allows treatment by coil embolization or decompression of venous trunks by stenting during the same intervention.…”
Section: Discussionmentioning
confidence: 99%
“…15 In Brazil, Malgor et al 16 report placing an IVC filter in a suprarenal position after cavography showed that the vessel was duplicated and also reported that the filter effectively prevented pulmonary embolism. 16 Although several different diagnostic methods are under analysis for their potential to identify and diagnose PVC, including transvaginal ultrasound, computed tomography, and magnetic resonance, 4,6 angiography is still the gold standard, for diagnosis both of PVC and of anatomic anomalies of the IVC and iliac veins, because it enables assessment of the different flow patterns and also allows treatment by coil embolization or decompression of venous trunks by stenting during the same intervention. 4,8,17 Certain angiographic criteria should be present to confirm a diagnosis of PVC, specifically: reflux demonstrated by proximal injection of contrast into the ovarian vein with filling of the distal ovarian venous plexus, incompetent pelvic veins with 5 to 10 mm diameters, flow stasis in the ovarian venous plexus, with visualization of pelvic veins at the median line, vulvovaginal, and proximal thighs.…”
Section: Discussionmentioning
confidence: 99%